2017
DOI: 10.1016/j.snb.2016.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Digitized molecular detection on off-the-shelf Blu-ray discs: Upgraded resolution and enhanced sensitivity

Abstract: Beyond the intrinsic capability of storing and archiving high-definition movies and games, off-the-shelf Blu-ray discs have been adopted for the preparation of molecular binding assays, which are subsequently read and quantitated with a standard computer drive in conjunction with the disc-quality check program. The performance of this digitized molecular detection system has been examined first with an artificial "ink assay" (an array of microsize ink dots) to define the quantitation capability and the lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The amount of surface-bound antibodies would be dictated by the relative abundance of free AFB1 and anti-AFB1 antibodies in the sample, which in turn determines the density of deposited Ag/Ag 2 O clusters as these metallic clusters would interrupt the laser reading and produce errors that can be quantitatively detected by an optical drive . For BD systems, reading errors are classified as either LDC (long distance code) or BIS (burst indicator code) errors; it was confirmed that the distribution and density of the resulting BIS errors are directly correlated with the physical position and “density” of the Ag/clusters on the enhanced binding strips. , …”
Section: Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The amount of surface-bound antibodies would be dictated by the relative abundance of free AFB1 and anti-AFB1 antibodies in the sample, which in turn determines the density of deposited Ag/Ag 2 O clusters as these metallic clusters would interrupt the laser reading and produce errors that can be quantitatively detected by an optical drive . For BD systems, reading errors are classified as either LDC (long distance code) or BIS (burst indicator code) errors; it was confirmed that the distribution and density of the resulting BIS errors are directly correlated with the physical position and “density” of the Ag/clusters on the enhanced binding strips. , …”
Section: Results and Discussionmentioning
confidence: 89%
“…9 For BD systems, reading errors are classified as either LDC (long distance code) or BIS (burst indicator code) errors; it was confirmed that the distribution and density of the resulting BIS errors are directly correlated with the physical position and "density" of the Ag/ clusters on the enhanced binding strips. 19,20 The performance of such an indirect competitive assay depends on both the surface coverage of immobilized AFB1-BSA and concentration of biotin-labeled antibodies, which essentially affects the sensitivity and dynamic response range. To achieve the optimal surface coverage of immobilized AFB1-BSA conjugates, different concentrations (0−100 μg/mL) of AFB1-BSA conjugates were examined with the same concentration of biotin-labeled antibodies (14 μg/mL; in the absence of free AFB1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The ECC-based method has been extended for applications such as onsite pregnancy test, 39 multiplexed drug abuse diagnostics, 40 heavy metal detection, 41 and acute myocardial infarction monitoring. 41 Furthermore, Blu-ray optical drives have been shown to increase the resolution and sensitivity for biosensing, 42,43 reaching a sensitivity and selectivity comparable to standard enzyme-linked immunosorbent assays.…”
Section: Applicationsmentioning
confidence: 99%
“…Some approaches deal with the application fields such as accelerometry, profilometry and linear measurements [13][14][15]. Latest research suggests that CD and DVD pick up heads have a lot of potential for the instrumentation development in biochemistry and biosensing [16,17]. However, it was not applied for the determination of an angle encoder disc surface quality measurements.…”
Section: ⇑ Corresponding Authormentioning
confidence: 99%